Carrefour : retailing in an international marketplace - Baack, Daniel W., (SAGE knowledge. Cases., 2016)
The French supermarket company, Carrefour, has grown to own a significant share of the global retail market. This case study examines how Carrefour has ensured its success in international markets by adapting its strategies, depending on local culture, economy or religious differences.